Carbon nanosheet-carbon nanocage encapsulated Cu composite from chemical vapor deposition of real-world plastic waste for tailored CO2 conversion to various products. (December 2021) - Chen, WenQian; Fu, Xiaoxu; Chan, Wei-Ping; Veksha, Andrei; Lisak, Grzegorz
Highlights: Cu/CNS was prepared via chemical vapor deposition from plastic waste in one step. Cu/CaO catalyzed the growth of carbon nanocages on Cu attached to carbon nanosheet. Carbon nanocages helped prevent Cu nanoparticles from aggregation and oxidation. Cu/CNS was efficient for electrochemical CO2 reduction reaction (CO2 RR). The CO2 RR performance of Cu/CNS was tailored by changing Cu/CaO synthesis methods. Abstract: Carbon nanosheet supported Cu (Cu/CNS) is an exemplary electrocatalyst for electrochemical CO2 reduction reaction (CO2 RR). The Cu/CNS electrocatalysts however suffer from agglomeration of dispersed Cu nanoparticles and restacking of CNS causing degradation of electrocatalytic activity. Here, a facile one-step method is proposed for manufacturing tailor-made Cu/CNS (e.g., where Cu particle size is stabilized by encapsulation into carbon nanocages (CNC) fixed to a porous and conductive CNS). The electrocatalysts were prepared via catalytic chemical vapor deposition over Cu loaded CaO (Cu/CaO) catalysts from recycled real-world plastic waste. The formation of CNC could help prevent restacking of CNS with specific surface area of around 200–400 m 2 g  −   1 and maintain good dispersion of Cu nanoparticles. The CO2 RR performance (including selectivity and current density) of Cu/CNS was conveniently controlled by the Cu/CaO preparation methods. Compared to Cu/CaO prepared via impregnation or with ethylene glycol, Cu/CaO synthesized via urea-assisted method catalyzed formation of Cu/CNS with improved CO selectivity at lower overpotential (maximum CO Faradaic efficiency was 82.1% at -0.76 V versus reversible hydrogen electrode), higher current density, and suppressed hydrocarbon selectivity owning to the electrocatalyst highest porosity and smallest Cu nanoparticles over CNS. Graphical abstract: Image, graphical abstract